PERBANDINGAN TUGAS MEDIATOR PADA PENGADILAN AGAMA INDONESIA DENGAN MAHKAMAH SYARIAH MALAYSIA - Mardalena Hanifah (Departemen Hukum Perdata, 2020)
Article 3 (2) Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures, Case Examining Judges in the consideration of a decision must state that the case has been pursued peace through mediation by mentioning the mediator. The court is not only tasked with examining, trying, and resolving cases it receives but also seeks to reconcile the parties. The court, which has been impressed as a law enforcement and justice institution, now appears as an institution that seeks peaceful solutions for the parties. The implementation of Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures in Courts can be an eff ort to resolve civil disputes so that the settlement of civil disputes through mediation is the main choice. The research method used is normative legal research which includes research on legal principles which is very basic in guided law. The nature of the research carried out is descriptive, namely research that describes and explains in clear and detailed sentences. The data used are secondary data obtained from literature, consisting of primary, secondary, and tertiary legal materials. Processing and data analysis used qualitative methods. The defi nition of mediation according to the Religious Courts in Indonesia and the Syari’ah Courts in Malaysia is the eff ort of the judges and courts to reconcile the parties so that the divorce process does not continue at the next trial. When the mediation process was carried out at the Indonesian Religious Court and the Syari’ah Court in Malaysia, there was a similarity, namely the mediation process was carried out at the fi rst trial and it was an obligation for the disputing parties in a divorce case to take mediation. according to the procedure for the appointment of mediators at the Indonesian Religious Courts and the Syari’ah Courts in Malaysia and the appointments of these mediators are both made by the judges.